Distribution of Zakat and The Empowerment of MSMEs in Bandungrejo: Experience of BAZNAS Malang - Galuh Widitya Qomaro; Maya Lestari (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Zakat is the main pillar that has a role for the Islamic economy. BAZNAS Malang has a very important role as a means of community welfare. One of them is for the Bandungrejo MSME community by distributing empowerment-based work tools. The research method of this article is qualitative. The main subject of MSMEs in Bandungrejo who received an empowerment program from BAZNAS Malang. Information was obtained through documentation, observation and interview techniques, as well as deductive data analysis techniques. The empowerment of MSMEs in Bandungrejo is carried out continuously. program planning that has been prepared must be able to function as a driving force so as to create a holistic community empowerment program. The existence of this program is also in line with the Islamic law, Law Number 23 of 2011 about Zakat Management and Government Regulation Number 14 of 2014 about Implementation of Law Number 23 of 2011 about Zakat Management which prioritizes the utilization of zakat for the welfare of the people and poverty alleviation. The economic empowerment of the people has been achieved based on the right and good goals and objectives. The author suggest for developing community resource training programs and special assistance so that the empowerment program runs optimally because cooperation from all elements of the government, private sector and community is able to maximize the welfare of the community.